Missense Mutations in NKAP Cause a Disorder of Transcriptional Regulation Characterized by Marfanoid Habitus and Cognitive Impairment - Fiordaliso, Sarah K; Iwata-Otsubo, Aiko; Ritter, Alyssa L; Quesnel-Vallières, Mathieu; Fujiki, Katsunori; Nishi, Eriko; Hancarova, Miroslava; Miyake, Noriko; Morton, Jenny E V; Lee, Sangmoon; Hackmann, Karl; Bando, Masashige; et al. (American journal of human genetics, 2019)
NKAP is a ubiquitously expressed nucleoplasmic protein that is currently known as a transcriptional regulatory molecule via its interaction with HDAC3 and spliceosomal proteins. Here, we report a disorder of transcriptional regulation due to missense mutations in the X chromosome gene, NKAP. These mutations are clustered in the C-terminal region of NKAP where NKAP interacts with HDAC3 and post-catalytic spliceosomal complex proteins. Consistent with a role for the C-terminal region of NKAP in embryogenesis, nkap mutant zebrafish with a C-terminally truncated NKAP demonstrate severe developmental defects. The clinical features of affected individuals are highly conserved and include developmental delay, hypotonia, joint contractures, behavioral abnormalities, Marfanoid habitus, and scoliosis. In affected cases, transcriptome analysis revealed the presence of a unique transcriptome signature, which is characterized by the downregulation of long genes with higher exon numbers. These observations indicate the critical role of NKAP in transcriptional regulation and demonstrate that perturbations of the C-terminal region lead to developmental defects in both humans and zebrafish.
Keywords: dánio pruhované; Animals; Histone Deacetylases; Cognitive Dysfunction; Repressor Proteins; P-complex; represorové proteiny; spliceosome; sekvence aminokyselin; Transcription, Genetic; lidé; histondeacetylasy; Mutation, Missense; Amino Acid Sequence; Zebrafish; splicing; regulace genové exprese; genetická transkripce; Down-Regulation; Genes, X-Linked; missense mutace; Exons; Sequence Alignment; transcriptome; kognitivní dysfunkce; exony; transkriptom; down regulace; Gene Expression Regulation; zvířata; Transcriptome; sekvenční seřazení; geny vázané na chromozom X; Humans